PENERAPAN MODEL STAD UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V MIN IE LEUBEUE - Muhammad Juned Basyah (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2018)
This study aims to improve the learning outcomes of 5th grade students of MIN Ie Leubeue through the application of the Student Teams Achievement Division (STAD) learning model. This type of research is Classroom Action Research. Data collection is carried out through preparation, implementation of actions, observation, and self-reflection. Data analysis is done descriptively. The results of data analysis show that the acquisition of student learning outcomes with an average value in cycle I the average value obtained by students is 68.13, cycle II the average value is 75.42 and cycle II the average value is 83.75. Student learning completeness in cycle I is 58.33%, cycle II is 79.17%, and cycle III is 95.83%. These it can be concluded, the implementation of STAD type Cooperative can improve student learning outcomes.